Better Functional Outcomes in Plate Fixation of Midshaft Clavicle Fracture in Dr. Soetomo General Academic Hospital - Edward, Mouli; Benedicta, Steesy; Wardhana, Teddy Heri ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2022)
Background: Clavicle fractures are common, with treatment trends shifting from conservative to operative. While malunion often has minimal functional impact, nonunion rates and associated complications remain a concern. This study evaluates functional outcomes between plating and conservative approaches for midshaft clavicle fractures.Methods: A total of 531 cases with a midshaft clavicle fracture presented to the emergency room between January 1, 2014 and December 31, 2018 at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Patients with a head injury, multiple traumas, re-fracture, malunion, open fracture, and pathological fracture were excluded. 161 patients remained. A conservative group (84 patients) was treated using an arm sling, and an operative group (77 patients) with Open Reduction and Internal Fixation (ORIF) and S-plate. Clinical and functional scores were evaluated retrospectively a minimum of 6 months after treatment. Shoulder function was evaluated using the Constant Shoulder Score and Manual Muscle Test.Results: 117 (72.7%) patients were male, with a mean age of 35.4 ± 12.33 years old. The right side was dominantly injured. The Manual Muscle Test score in the operative group was five, and in the conservative group, four. The Constant Shoulder score in the operative group was 93.38 ± 7.529, and in the conservative group, 86.60 ± 7.560 (p < 0.001). The DASH score in the operative group was 10.05±6.98 and in the conservative group, 23.67±3.49 (p < 0.001).Conclusion: In our study, surgery on clavicle midshaft fractures showed significant improvement and satisfaction compared to conservative treatment. Patients gained better function.